1979
DOI: 10.2134/agronj1979.00021962007100020010x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Soil Acidity in Symbioses of Mung Bean with Rhizobia1

Abstract: Variation in tolerance of soil acidity among 40 rhizobial strains was assessed in greenhouse trials in which the strains were applied as separate seed inoculants (5 ✕104 cells per seed) to two cultivars of mung bean (Vigna radiata L.) and performance was measured by nodulation, growth, and N‐yield of the host plant. The plants grew in a low N, low Ca acid subsoil, Goldridge fine sandy loam (Typic Hapludult, fine loamy, mixed, mesic), left at its natural pH of 5.0 (saturation paste) or limed with CaCO3 to pH 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…High (not extreme) soil temperatures will delay nodulation or restrict it to the subsurface region (133). Munns et al (221) found that alfalfa plants grown in desert environments in California maintained few nodules in the top 5 cm of soil but were extensively nodulated below this depth. Nodulation of soybean was markedly inhibited at 42 and 45°C during 12-h and 9-h days, respectively (186), with no correlation between the ability of plant strains to grow at high temperature and to induce nodulation under temperature stress.…”
Section: High Temperature and Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…High (not extreme) soil temperatures will delay nodulation or restrict it to the subsurface region (133). Munns et al (221) found that alfalfa plants grown in desert environments in California maintained few nodules in the top 5 cm of soil but were extensively nodulated below this depth. Nodulation of soybean was markedly inhibited at 42 and 45°C during 12-h and 9-h days, respectively (186), with no correlation between the ability of plant strains to grow at high temperature and to induce nodulation under temperature stress.…”
Section: High Temperature and Heat Stressmentioning
confidence: 99%
“…The host cultivar-rhizobial strain interaction at acid pH has also been investigated. Munns et al (221) noted that nodulation and nitrogen fixation by some strains of Bradyrhizobium at acidic pH differ with the cultivar of mung bean used. Vargas and Graham (327) examined the cultivar and pH effects on competition for nodule sites between isolates of Rhizobium in beans (P. vulgaris) under acidic conditions.…”
Section: Soil Acidity and Alkalinitymentioning
confidence: 99%
“…Inoculation of legumes with exotic strains of rhizobia is a common agricultural practice intended to promote nitrogen fixation and increase crop yield. Despite improvements in inoculation methods (3,13,31,34) and selection of rhizobial strains for increased nitrogen fixation capacity (16), competitive ability (1), and ability to withstand environmental stress (15,17,19), inoculation does not always lead to increased plant growth and crop yield.…”
mentioning
confidence: 99%
“…Evidence has been presented that many legumes are more sensitive to acidity when dependent on N2 fixation than when grown on combined nitrogen (2). This has been explained as being due to the sensitivity to acid conditions of either nodule function (21,22) or the initiation and development of nodulation (14,18). It is not surprising, therefore, that amelioration of soil acidity with lime is often (though not always) beneficial to the growth of many legumes (20).…”
mentioning
confidence: 99%